Model Pembelajaran Ilmu Sharaf dengan Menggunakan Metode Inquiry dan Metode Snowball Tashrif: di Jurusan Pendidikan Bahasa Arab UIN Maulana Malik Ibrahim Malang - Siti Durotun Naseha; Muassomah Muassomah (Prodi Pendidikan Bahasa Arab FTK UIN Sunan Ampel, 2018)
The aim of this study is to apply Sharaf learning to students after using the Inquiry model with Tashrif Snowball method. The study was conducted at Department of Arabic Education in UIN Malang. This study used quantitative and qualitative methods with the Classroom Action Research / PTK approach. The data collection process used the method of observation, interviews, and documentation. The research instrument used the observation sheet of accomplishment. The results of this study the feasibility of seeing from the processes in cycles 1 and 2 and the results are; 45.5% to 81.8% understand the material, then from 36.4% to 13.6% do not understand the material yet and 18.1% to 4.6% do not understand the material. In conclusion, the implication of the Inquiry method is students' results have improved and have become accustomed to thinking critically about the sub- material of sharaf learning. In addition. It can be concluded that the inquiry learning model with the Snowball Tashrif method is good to be applied in Sharaf learning.